2021
DOI: 10.48550/arxiv.2103.04015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Resource Management for Providing QoS in Drone Delivery Systems

Abstract: Drones have been considered as an alternative means of package delivery to reduce the delivery cost and time. Due to the battery limitations, the drones are best suited for lastmile delivery, i.e., the delivery from the package distribution centers (PDCs) to the customers. Since a typical delivery system consists of multiple PDCs, each having random and time-varying demands, the dynamic drone-to-PDC allocation would be of great importance in meeting the demand in an efficient manner. In this paper, we study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Hence, there is no uncertainty about this cell, and the value of uncertainty is 0. However, as t increases, the value uncertainty increases based on (3). When the value of t becomes sufficiently large, the uncertainty tends to 1.…”
Section: B Uncertainty Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, there is no uncertainty about this cell, and the value of uncertainty is 0. However, as t increases, the value uncertainty increases based on (3). When the value of t becomes sufficiently large, the uncertainty tends to 1.…”
Section: B Uncertainty Modelmentioning
confidence: 98%
“…Unmanned aerial vehicles (UAVs) have recently attracted considerable interest in a wide range of applications. Aerial reach, high mobility, and cost-effective deployment are the key features that make the UAVs an ideal candidate for applications such as drone delivery [1]- [3], search and rescue [4], [5], wireless communications [6]- [8], and mapping, tracking, and monitoring [9]- [11]. UAV-assisted traffic monitoring in urban areas is another emerging application that can play a key role in intelligent transportation systems (ITSs) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing customer waiting cost is an important goal of vehicle-UAV delivery [58], but scholars pay extra attention to it. Khamidehi et al [59] found that it is more reasonable to provide a probabilistic upper-bound on the queue length of the packages waiting to be delivered. Boyles and Zhu [60] embedded the waiting cost as a sub-problem into the electric vehicle route.…”
Section: Introductionmentioning
confidence: 99%